2008
DOI: 10.1007/s00595-007-3726-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy in patients with a history of gastrectomy

Abstract: Laparoscopic cholecystectomy is a safe and effective treatment for symptomatic gallstone disease in patients with a history of gastrectomy, although previous gastrectomy is associated with an increased need for adhesiolysis and a longer operative time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 10 publications
2
39
0
Order By: Relevance
“…Therefore, if cholecystectomy is performed by a skilled surgeon, the procedure can be carried out safely in patients with a history of gastric cancer operation. 5,6 Furthermore, in the present study, the open conversion among 45 patients with UAS history occurred in only 2 cases (4.4%), which is comparable to other studies. 5,6 In the present study, there were no significant differences in hospital stay or complication incidence between the UAS and non-UAS groups.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Therefore, if cholecystectomy is performed by a skilled surgeon, the procedure can be carried out safely in patients with a history of gastric cancer operation. 5,6 Furthermore, in the present study, the open conversion among 45 patients with UAS history occurred in only 2 cases (4.4%), which is comparable to other studies. 5,6 In the present study, there were no significant differences in hospital stay or complication incidence between the UAS and non-UAS groups.…”
Section: Discussionsupporting
confidence: 78%
“…3 However, as this field has continued to advance, there have been reports suggesting that LC can be safely performed even in patients who underwent prior UAS. [4][5][6] Past studies have encouraged authors to perform LC in most patients who underwent prior UAS. Past studies have demonstrated the safety of LC in patients who underwent prior UAS, and this approach is generally used in patients with a UAS history.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors advocated prophylactic cholecystectomy, simultaneous removal of the gallbladder during gastric resection to prevent potential gallstone-related sequelae, such as cholecystitis, cholangitis, and pancreatitis [8]. This approach also avoided the possibility of subsequent cholecystectomy, which might be difficult owing to potential adhesion at the upper abdomen caused by previous gastrectomy and lymph node dissection [9]. A multicenter, randomized controlled trial, the Cholegas study, was initiated in November 2008 to evaluate prophylactic cholecystectomy; however, the final result has not been disclosed yet [10].…”
Section: Introductionmentioning
confidence: 99%
“…Due to such higher rate of gallstones, some Authors proposed prophylactic cholecystectomy, advocating that concomitant cholecystectomy is not time consuming and substantially with minimal additional risks for the patients [14][15][16], while subsequent cholecystectomy (in most cases attempted laparoscopically) is known to be more challenging after gastric surgery, with an increased risk of conversion, bile duct injuries and a longer operating time [17,18]. Another advantage of prophylactic cholecystectomy was represented by the avoidance of a possible reintervention in case of acute post-operative cholecystitis [7,19,20] and the avoidance of difficult procedures like endoscopic retrograde cholangiography (ERC) in the presence of Roux-en-Y reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, not all the patients who are diagnosed to have cholelithiasis after gastric cancer surgery will develop symptoms or require additional surgical treatments [2][3][4] and a standard laparoscopic cholecystectomy is feasible even in those patients who underwent previous gastric surgery [17,21]. Moreover, in recent years, the problem of litigation and malpractice claims have raised the issue of removing a normal organ for prophylaxis of any benign disease.…”
Section: Introductionmentioning
confidence: 99%